2022
DOI: 10.3390/nu14194126
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Polaprezinc-Based Therapy versus the Standard Triple Therapy for Helicobacter pylori Eradication: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Helicobacter pylori (H. pylori) is the most prevalent etiology of gastritis worldwide. H. pylori management depends mainly on antibiotics, especially the triple therapy formed of clarithromycin, amoxicillin, and proton pump inhibitors. Lately, many antibiotic-resistant strains have emerged, leading to a decrease in the eradication rates of H. pylori. Polaprezinc (PZN), a mucosal protective zinc-L-carnosine complex, may be a non-antibiotic agent to treat H. pylori without the risk of resistance. We performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…Several investigations have demonstrated that anti-helicobacter drugs such as levofloxacin have higher bacterial toxicity when combined with Resveratrol and its derivatives ( Bouarab Chibane et al, 2019 ; Di Lodovico et al, 2019 ; Di Fermo et al, 2020 ). Polaprezinc (PZN) or zinc carnosine (L-carnosine) are zinc chelate compounds that protect the digestive mucosa ( Mahmoud et al, 2022 ). This antioxidant compound is particularly efficient in protecting against H. pylori and promoting ulcer healing, and unlike other antibiotics, it does not cause drug resistance ( Teng et al, 2020 ; Ibrahim et al, 2022 ; Mahmoud et al, 2022 ).…”
Section: Alternative Therapiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several investigations have demonstrated that anti-helicobacter drugs such as levofloxacin have higher bacterial toxicity when combined with Resveratrol and its derivatives ( Bouarab Chibane et al, 2019 ; Di Lodovico et al, 2019 ; Di Fermo et al, 2020 ). Polaprezinc (PZN) or zinc carnosine (L-carnosine) are zinc chelate compounds that protect the digestive mucosa ( Mahmoud et al, 2022 ). This antioxidant compound is particularly efficient in protecting against H. pylori and promoting ulcer healing, and unlike other antibiotics, it does not cause drug resistance ( Teng et al, 2020 ; Ibrahim et al, 2022 ; Mahmoud et al, 2022 ).…”
Section: Alternative Therapiesmentioning
confidence: 99%
“…Polaprezinc (PZN) or zinc carnosine (L-carnosine) are zinc chelate compounds that protect the digestive mucosa ( Mahmoud et al, 2022 ). This antioxidant compound is particularly efficient in protecting against H. pylori and promoting ulcer healing, and unlike other antibiotics, it does not cause drug resistance ( Teng et al, 2020 ; Ibrahim et al, 2022 ; Mahmoud et al, 2022 ). PZN has been shown in several trials to be useful in reducing apoptosis and inflammation, healing skin and stomach wounds, and preserving tight junctions ( Furihata et al, 2020 ; Ibrahim et al, 2022 ).…”
Section: Alternative Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1995, Kuwayama was the first to report the effectiveness of polaprezinc in eradicating H. pylori [20]. Subsequently, the efficacy of polaprezinc as an add-on to triple therapy comprising lansoprazole, amoxicillin (AMX), and CAM was reported [21,22]. These reports described eradication therapy using PPIs.…”
Section: Introductionmentioning
confidence: 99%